Prospects of the use of lithium-ion battery vehicles and sustainable development in South America - Romero-Carrion, Violeta Leonor (2023)
South America has the lithium deposits that enable economic growth in the region, given the global demand for manufacturing batteries for electric vehicles, which reduce greenhouse gas emissions. The objective is to determine the relationship between the use of lithium-ion battery vehicles and the components of sustainable development in South America. The design is non-experimental, correlational, and analytical. The sample comprises Argentina, Bolivia, Chile, and Peru. A documentary analysis was conducted, and a hypothesis test statistic was applied based on the data found in the literature. The results show that by the year 2034, sales of electric vehicles will continue to grow at an annual rate of 25.2%. The application of Spearman's Rho confirms a significant correlation between the type of energy (fossil and electric) used by vehicles and their CO2 eq emissions. However, the current regulations in the region do not facilitate effective management of the lithium value chain. There are social conflicts related to the use of water in lithium extraction, noncompliance with agreements by operating companies, and a lack of transparency, leading to the cancellation or suspension of 50% of mining projects.